A nonlinear model to apply beam-column joint shear failure in analysis of RC moment resisting frames. (December 2019) - Najafgholipour, M.A.; Arabi, A.R.
Abstract: Principal Tensile Stress (PTS) formulation, along with Diagonal Strut simulation technique, is known as a practical method for considering Reinforced Concrete (RC) beam-column joint panel deformation as well as undesirable brittle joint shear failure mode in the nonlinear analysis of RC frames. The tensile strength of the joint core and nonlinear shear stress-deformation of the joint panel are two key parameters in the modeling procedure. In this article, a formulation is developed to estimate the joint core tensile strength corresponding to the ultimate shear strength by employing a detailed Finite Element Modeling (FEM) technique and through a comprehensive numerical study. The proposed equation takes into account the influential properties of the joint core including concrete compressive strength, beam and column dimensions, joint panel aspect ratio, and beam flexural reinforcement ratio. Furthermore, based on the nonlinear shear behavior of the joint panels resulted from the numerical investigation in the current study, a multi-linear curve is suggested for the tensile stress-shear deformation of the joint panels. The proposed model is also implemented in nonlinear frame analysis software SAP2000. The results of simulation and analysis of three connections with various governing failure modes using the proposed simplified technique showed its capability in capturing different failure modes in the joint region.